Studi Literatur: Merancang Design UI/UX untuk Pet Parents dalam Memelihara Hewan Peliharaan (Anjing dan Kucing) Menggunakan Metode Narrative Review - Emellika Rahmayana (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Currently, many people keep cats and dogs at home, in fact, according to research, keeping cats and dogs can relieve stress for pet parents. Cats and dogs are no longer just pets but are like family for pet parents. Veterinarians and pet shops are everywhere, this indicates that many people are starting to keep and love their cats and dogs. The need for technology regarding pets is also increasing, encouraging people involved in the IT world to create applications. One of the needs is how to design the right UX/UI for an application related to pets, especially cats and dogs. The intended users are pet parents. How can it be easy for pet parents to use this application so that pet parents get a user experience and user interface that is comfortable and enjoyable so that the purpose of creating the application can be achieved well. Comparing the 10 selected journals according to the criteria using the narrative review method, it was found that the second journal was the best among the other nine journals.